FEED INTAKE, ABSORPTION, CONVERSION AND GROWTH OF FRY AND FINGERLINGS OF ROHU LABEO ROHITA (HAMILTON) - Singh, B N; Sinha, V R P; Chakraborty, D P (Indian Journal of Fisheries, 2011)
A mixturre of fishmeal plus groundnut oilcake plus wheat bran and yeastin a ratio 25 : 65 : 5(10) : 5, having a protein content of about 45%, was foundto bs better utilized and gave significantly tetter conversion rate than the conventionalfeed, a mixture of gixjundinut oilcake and wheat bran in the proportioci 1 : 1,indicating that the bran portion of the conventional feed may be succesrfuHyreduced and flsbmeal added to its place for obtaining significantly higheir rate ofgrowth. The yeast increased the aoceptibility and conversion of feeds. The effectsof oxygen content in water on rates of feed intake, absorption and growth arealso discussed.